State dependence in Swedish social assistance in the 1990s: What happened to those who were single before the recession? - Daniela Andrén; Thomas Andrén (Örebro University School of Business, 2013)
Using a dynamic discrete choice model that controls for unobserved heterogeneity and the initial conditions problem, we estimate the state dependence in Swedish social assistance for Swedish-born and foreign-born who were single in 1990 before the recession period started. The estimates of the structural state dependence for Swedish-born singles indicate that it is unaffected by the event of living together with a partner, and the effect is significantly lower for women than for men. For the foreign-born singles, the state dependence for those who stay single the whole decade is equally strong for men and women, and almost not affected when the foreign-born single started to live together with a foreign-born partner.
Keywords: I30; I38; J18; 330; social assistance; state dependence; country of birth; singles; married/cohabitated; unobserved heterogeneity; initial conditions; dynamic random effects probit model; GHK simulator